1980
DOI: 10.1093/nar/8.16.3517
|View full text |Cite
|
Sign up to set email alerts
|

Salt induced transitions of chromatin core particles studied by tyrosine fluorescence anisotropy

Abstract: Chromatin core particles containing 146 base pairs of DNA have been found to undergo a single defined transition below 10 mM ionic strength as studied by both sedimentation velocity and tyrosine fluorescence anisotropy. A method is described for the preparation of such core particles from chicken erythrocytes with greater than 50% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 44 publications
(37 reference statements)
5
70
1
1
Order By: Relevance
“…The wrapped phase can occur again with a minimum chain length and salt screening parameter (e.g., for fixedZ = 1 and for a mechanically flexible chain, these minimum values are given byL = L/R s = 5.57 andκ = κR s > 1, respectively). The wrapped phase is thus predicted to occur at intermediate salt concentrations or sufficiently large sphere charge in agreement with previous studies [37, 38, 63, 67, 68, 70-72, 78, 95] and also recent experiments [1,3,11,16,17,44,45,[79][80][81][82][83][84][85][86][87].…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The wrapped phase can occur again with a minimum chain length and salt screening parameter (e.g., for fixedZ = 1 and for a mechanically flexible chain, these minimum values are given byL = L/R s = 5.57 andκ = κR s > 1, respectively). The wrapped phase is thus predicted to occur at intermediate salt concentrations or sufficiently large sphere charge in agreement with previous studies [37, 38, 63, 67, 68, 70-72, 78, 95] and also recent experiments [1,3,11,16,17,44,45,[79][80][81][82][83][84][85][86][87].…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…It was shown that a minimal chain-sphere model for nucleosome core particles [37][38][39][40][41]51] can closely predict the experimentally observed [79][80][81][82][83][84][85][86][87] salt-induced wrapping-unwrapping behavior of these complexes based on an interplay between two competing mechanisms: the electrostatic attraction of DNA (modeled as a negatively charged worm-like chain) with the histone core (modeled as a positively charged nano-sphere), which favors DNA adsorption and wrapping around the sphere, and the mechanical bending stiffness of the DNA and its electrostatic self-repulsion, which favor unwrapping and even dissociation of the DNA from the complex. The experimental stability diagrams [45] also exhibit an association (or complexation) equilibrium between nucleosome core particles and the free DNA and free histones in an electrolyte solution in the regime of moderately large values of core particle and salt concen-tration.…”
Section: Introductionmentioning
confidence: 95%
“…In a few experiments, 10 mM Tris/HCl (pH 7.5) was used; the structures observed in Tris buffer were indistinguishable from those in triethanolamine buffer. When desired, chromatin was stripped of histones H1 and H5 (29).…”
Section: Methodsmentioning
confidence: 99%
“…In a few experiments, 10 mM Tris/HCl (pH 7.5) was used; the structures observed in Tris buffer were indistinguishable from those in triethanolamine buffer. When desired, chromatin was stripped of histones H1 and H5 (29).Glutaraldehyde fixation of chromatin in the various salt concentrations was done as described (8,30); the fixed preparations were dialyzed extensively versus triethanolamine buffer and were stored on ice.Scann-ng Force Mkroscopy (SFM) Imain. Fibers were deposited on cover glass cleaned by prebaking for 5 min at 600°C.…”
mentioning
confidence: 99%
“…Chromatin (0.1 mg/ml) in the above buffers, containing 0, 10, or 80 mM NaCl, was fixed with 0.1% (vol/vol) glutaraldehyde overnight at 49C and then dialyzed extensively versus 10 mM Tris/HCI (pH 7.5) and stored on ice. Chromatin depleted ofhistones Hi and H5 was obtained by stripping the linker histones with 0.35 M NaCl in the presence of CM-Sephadex C25 (Pharmacia) (6).…”
Section: Chicken Erythocyte Crmentioning
confidence: 99%